Investigation on geological structure and geothermal resources using seismic exploration. (December 2022) - Liu, Fei; Long, Xiting
Highlights: Micro-logging and small refraction were conducted to determine observation system and static correction models. 3D Monte Carlo high-precision residual static correction was used to gain a better SNR. The potential location of geothermal resource and exploration holes were calibrated. Abstract: Seismic exploration was used to investigate geological structure and potential location of geothermal resources in Xian County, North China. The velocity structure survey near surface was conducted by micro-logging and small refraction to determine the observation system and static correction models. Two test sections and many of test points were designed to get the best experimental parameters. The static correction was used to eliminate surface differences accompanied with deconvolution to improve resolution, and the high-precision velocity analysis and three-dimensional Monte Carlo high-precision residual static correction were used to obtain a better signal-to-noise ratio (SNR). The imaging section was converted into geological model in the working area by seismic interpretation technologies. The general morphology and buried depth of the main interfaces in each layer were obtained by using the seismic exploration methods. The potential location of geothermal resource was predicted mainly in Jixianian of Proterozoic of the Middle Upper and the Cambrian Ordovician of Paleozoic and the favorable location of two exploration boreholes were calibrated based on these analyses.